From Compliance to Collaboration to Culture: A Prospective Evaluation of the HIPESAC Timeout and Patient Safety Advocate Platform - James F. Schlund; Ashley Davis; Linda Esparza; Sadie M. Voigtlander (American Journal of Medical Quality, 2026)
Background: The Universal Protocol has standardized pre-procedural verification since 2004, yet procedural sentinel events persist; 127 wrong-surgery events were reported nationally in 2024. Compliance-based checklists may be insufficient for the human-factors environment of complex procedural care. Methods: In a prospective 3-phase quality improvement evaluation at a rural health system, we tested an enhanced timeout (HIPESAC) in which the proceduralist presents and justifies each verification element to the full team, any member empowered to question, correct, or halt the procedure. For high-risk cases, an expanded Patient Safety Advocate (PSA) protocol adds voicing of concerns from least to most senior, with a designated patient advocate issuing consent to proceed. Phase 1 piloted 4 PSA-activated procedures; Phase 2 audited 20 with surveys; and Phase 3 evaluated the standard timeout across 22 procedures. Results: The platform identified latent threats before initiation: material readiness events in 8 of 20 high-risk procedures (40%; one critical absent item, 7 proactive adjustments) and 9 process deficiencies across 22 standard procedures. The timeout added a median of 54 seconds. Surveys indicated high acceptance among respondents, with unanimous endorsement of speaking-up empowerment. In 2 cases—one per tier—a non-proceduralist surfaced information that altered the procedure. Conclusions: The platform was feasible, well accepted, and surfaced latent procedural threats in this single-center evaluation. By requiring the proceduralist to present to the team and, at higher risk, inverting the order of voice, it may operationalize authority-gradient inversion as an intrinsic feature. Multi-site controlled evaluation is warranted.